Определение группового углеводородного состава нефтяных фракций по их физико-химическим характеристикам - Лабецкая Е. А. Елена Анатольевна; Федоров А. Ф. Анатолий Федорович; Сваровская Н. А. Наталья Алексеевна; Тихоненко Л. А. Лариса Александровна ([Б. м.], [1989])
Деп. в ЦНИИТЭХНефтехим, 15.05.85, № 133-НХ-89.